PROJECT-BASED LEARNING WITH AI-INTEGRATION TO FOSTER CRITICAL THINKING SKILLS AND SELF-EFFICACY OF PRE-SERVICE TEACHERS - Harahap, Dahrul Aman; Faizin, Muhammad; Erydani, Vinsensia Anisa Citta; Lestari, Sri; Dewi, Desi Surlitasari; Ardhi, Mega Aulia (Universitas Labuhanbatu, 2025)
Purpose – This study aimed to evaluate the usefulness of Project-Based Learning (PjBL) combined with artificial intelligence (AI) tools in enhancing pre-service teachers' critical thinking and self-efficacy inside an instructional design course.Methodology – A pre-experimental one-group pretest-posttest design was applied. The study involved 46 pre-service teachers engaged in an instructional design course at a private university in Indonesia, chosen using purposive sampling. Two instruments were used: a 25-item critical thinking questionnaire and a 10-item self-efficacy scale. Normality tests were conducted, followed by paired-sample t-tests to determine differences between pre-test and post-test scores.Findings – The findings showed a statistically significant improvement in both critical thinking (t = -116.464, p < .001) and self-efficacy (t = -56.328, p < .001) after the AI-supported PBL intervention. The normality assumptions were met, and the effect size was notably strong for both variables. These results suggest that incorporating AI technologies into project-based learning can significantly improve pre-service teachers' cognitive and emotional preparedness for future teaching practices.Contribution – This study contributes to the teacher education literature by providing empirical evidence for the integration of AI technologies in project-based learning, promoting critical thinking and self-efficacy. It offers practical insights for instructional designers and educators seeking to equip future teachers with the competencies required in technologically rich educational environments.